‘Once a sex offender always a sex offender’?: essentialism and attitudes towards criminal justice policy - De Vel-Palumbo, Melissa (Psychology, crime & law, 2019)
The present research explores the proposition that psychological essentialism determines how we understand the nature of some types of crime and associated attitudes regarding how perpetrators should be treated. Specifically, we argue that people believe certain crimes are highly essentialized, and they treat offenders in those categories more punitively. Study 1 assessed the applicability of essentialism to crime, demonstrating that different types of crime are indeed more essentialized than others. Two additional studies demonstrated that essentialism beliefs play a unique role in individuals’ endorsement of policies regarding treatment of offenders who commit crimes of a sexual nature. We consider the implications of our findings for offender rehabilitation and reintegration.